Expert assessment of the impact of ship-strikes on cetacean welfare using the Welfare Assessment Tool for Wild Cetaceans. (23rd February 2023) - Rae, Francesca; Nicol, Christine; Simmonds, Mark P
Abstract: Human activities are increasingly impacting our oceans and the focus tends to be on their environmental impacts, rather than consequences for animal welfare. Global shipping density has quadrupled since 1992. Unsurprisingly, increased levels of vessel collisions with cetaceans have followed this global expansion of shipping. This paper is the first to attempt to consider the severity of ship-strike on individual whale welfare. The methodology of the 'Welfare Assessment Tool for Wild Cetaceans' (WATWC) was used, which is itself based upon the Five Domains model. Expert opinion was sought on six hypothetical but realistic case studies involving humpback whales ( Megaptera novaeangliae ) struck by ships. Twenty-nine experts in the cetacean and welfare sector took part. They were split into two groups; Group 1 first assessed a case we judged to be the least severe and Group 2 first assessed the most severe. Both groups then additionally assessed the same four further cases. This was to investigate whether the severity of the first case influenced judgements regarding subsequent cases (i.e. expert judgements were relative) or not (i.e. judgements were absolute). No significant difference between the two groups of assessors was found; therefore, the hypothesis of relative scoring was rejected. Experts judged whales may suffer some level (>1) of overall (Domain 5) harm for the rest of their lives following a ship-strike incident. Health, closely followed by Behaviour were found to be the welfare aspects most affected by ship-strikes. Overall, the WATWC shows a robust potential to aid decision-making on wild cetacean welfare.